Pregnancy in a Previously Conjoined Thoracopagus Twin with a Crisscross Heart - Bassam H. Rimawi; Iris Krishna; Anurag Sahu; Martina L. Badell (Hindawi Limited, 2015)
Background. Crisscross heart (CCH) is a complex, rare, congenital, rotational, cardiac abnormality that accounts for <0.1% of congenital heart defects (CHD). CCH is characterized by the crossing of the inflow streams of the two ventricles due to an abnormal twisting of the heart. A case of maternal CCH has not been previously reported. Case. We report a case of a primigravida with a CCH, who was separated at birth from her thoracopagus conjoined twin. Pregnancy was managed by congenital cardiology, maternal-fetal medicine, anesthesiology, and obstetrics. She underwent a 39-week vaginal delivery without maternal or neonatal complication. Conclusion. A successful term pregnancy outcome was achieved in a patient with CCH using a multidisciplinary approach to address her cardiac condition.